Determinants of Clean Water Accessibility at Muhammad Ali Kasim General Hospital, Gayo Lues: A Comprehensive Analysis - Manisha, Manisha; Arnis, Julita; Marta, Syunaha (Hasanuddin Medan, 2024)
Introduction: The hospital staff exert an impact on the accessibility of potable water inside the hospital premises. The provision of uncontaminated water is crucial for the provision of essential services in hospitals. Both the quality and quantity of water must meet stringent standards to prevent the spread of infections and diseases within the hospital premises. Similarly, efficient drainage systems are necessary to ensure proper water distribution. Goal: Determine the variables that influence the accessibility of uncontaminated water at the Muhammad Ali Kasim Gayo Lues General Hospital in 2023. Method: This study employs an analytical survey research method utilizing a cross-sectional methodology. The research population consisted of 300 officers and personnel at the hospital. A sample of 75 individuals was selected using the Slovin formula approach. The data analysis included both univariate and bivariate analysis, utilizing logistic regression test statistics. The Analysis Result: The chi-square test analysis revealed that the p-values for each variable were as follows: p-value = 0.010 for method, p-value = 0.000 for machine, p-value = 0.000 for material, and p-value = 0.003 for money. Conclusion: The availability of clean water is influenced by factors such as human activity, techniques used, machinery involved, materials used, and financial resources. It is expected that the hospital will prioritize and foresee the provision of water inside the hospital premises to provide an adequate and high-quality supply for everyday activities.